Emotional intelligence and internet addiction among students in The University (2020)
Uncontrollable usage of internet has become a psychosocial disorder that every professional should pay attention to. Many st internet addiction among students, medical doctors and librarians. Therefore, this study examined emotional intelligent utilisation) as correlates of internet addiction among students of the University of Ibadan. Descriptive survey of correlation ty sampling procedure to select 120 students (75 males and 45 females) with age range between 16-48 years. The Schutte e addiction scale (r = 0.89) were used to collect data for the study. Research questions were answered and tested. The find students was high ( = 2.19). In the level of emotional intelligent factors, emotional regulation was moderate ( = 2.57), e emotional utilisation was low (= 2.06). There was significant relationship between emotional expression (r = .232, P < .05), and > p <.05) and internet addiction while there was no significant relationship between emotional regulation and internet addic contribute to internet addiction. Adjusted R2 = .033; F3,96 = 2.113 and accounted for 6.2% contributions. Emotional regulation .103, P> .05) and emotional utilisation ( = .152, P>.05) did not relatively contribute to internet addiction. Students’ emotion contribute to internet addiction of students of the University of Ibadan. Students should be exposed to training on emotional e control their use of internet on daily basis.